2021
DOI: 10.1177/00220345211009449
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota May Mediate the Influence of Periodontitis on Prediabetes

Abstract: Mounting evidence has shown that periodontitis is associated with diabetes. However, a causal relationship remains to be determined. Recent studies reported that periodontitis may be associated with gut microbiota, which plays an important role in the development of diabetes. Therefore, we hypothesized that gut microbiota might mediate the link between periodontitis and diabetes. Periodontitis was induced by ligatures. Glycemic homeostasis was evaluated through fasting blood glucose (FBG), serum glycosylated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 35 publications
1
48
2
1
Order By: Relevance
“…Lachnospira , Ruminococcus , Erysipelotrichaceae , Eubacterium , and Ruminococcus 1 were butyrate producers. 15 , 16 Our results showed that all these microbes were decreased. Therefore, we speculated that these decreased microbes cause VKH disease by downregulating Treg cells.…”
Section: Discussionmentioning
confidence: 50%
“…Lachnospira , Ruminococcus , Erysipelotrichaceae , Eubacterium , and Ruminococcus 1 were butyrate producers. 15 , 16 Our results showed that all these microbes were decreased. Therefore, we speculated that these decreased microbes cause VKH disease by downregulating Treg cells.…”
Section: Discussionmentioning
confidence: 50%
“…Several studies have examined the gut microbiota of ligature-induced periodontitis mice [119,173,174]. One study reported that Parabacteroides and Desulfovibrionaceae increased and several butyrate-producing bacteria decreased significantly in the gut microbiota of ligature-induced periodontitis mice compared to control mice, and alpha-diversity of the gut microbiota in the periodontitis mice was significantly reduced compared to that of control mice [174].…”
Section: Microbiology 71 Oral and Gut Microbiota In Ligature-induced Periodontitis Modelmentioning
confidence: 99%
“…Several studies have examined the gut microbiota of ligature-induced periodontitis mice [119,173,174]. One study reported that Parabacteroides and Desulfovibrionaceae increased and several butyrate-producing bacteria decreased significantly in the gut microbiota of ligature-induced periodontitis mice compared to control mice, and alpha-diversity of the gut microbiota in the periodontitis mice was significantly reduced compared to that of control mice [174]. In addition to the study that investigated the bacterial composition of the gut microbiota by 16S rDNA sequencing, the Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) software was used to predict metagenome function from the 16S rDNA data [173].…”
Section: Microbiology 71 Oral and Gut Microbiota In Ligature-induced Periodontitis Modelmentioning
confidence: 99%
“…Ligation of maxillary second molars in mice is a common periodontitis modeling method. Many articles on periodontitis models have adopted the method of ligating maxillary second molars ( Li et al., 2021 ). Compared with first molars, ligating the second molar is more solid and suture is not easy to slip off.…”
Section: Discussionmentioning
confidence: 99%